Respuestas

  • Usuario de Brainly
2013-03-19T17:35:03+01:00

A) 2x - 6 = 8

    2x = 8 + 6

    2x = 14

    x= 14/2

    x = 7......R/.

 

B) x - 8 = 6 - 21

    x = 6 - 21 + 8

    x = -7......R/.

 

C) 5 + x = 2x + 1

     x - 2x = 1 - 5

    -x = -4

    x= -4 / -1

    x = 4......R/.

 

D) 5x - 2 = 3x -16

     5x - 3x = -16 + 2

     2x = -14

     x = -14 / 2

     x = -7.....R/.

 

E) 4 + 3x - 2(x - 1) = 2

     4 + 3x -2x + 2 = 2

     6 + x = 2

     x = 2 - 6

     x = -4.....R/.

 

F) 2(1 - 2x) + 3(3x - 2) = x - 1

    2 - 4x + 9x - 6 = x - 1

    -4 + 5x = x - 1

    5x - x = -1 + 4

    4x = 3

     x = 3/4